The effect of a preceptorship programme on newly hired experienced professional nurses' self-efficacy in nursing clinical competency in Saudi Arabia - Elizabeth Chipwanya; Charlene Downing; Elizabeth Nkosi (Elsevier, 2024)
Aim: This study aimed to determine if participation in a preceptorship programme affected newly hired experienced professional nurses' self-efficacy in clinical practice and whether their perceived competence was related to respondents' demographic profiles at a university hospital in Saudi Arabia. Background: Formal preceptorship programmes are initiated with the aim of improving the characteristics related to new workplace adaptations, such as reducing stress and anxiety, improving effective communication, enhancing clinical performance and competencies, and learning new clinical skills. These programmes' effectiveness in improving nurses' self-efficacy in clinical practice is seldom measured, especially among newly hired experienced professional nurses. Methods: A quasi-experimental, quantitative pre- and post-test one-group study design with convenient sampling was used. Results: Self-efficacy post-test scores were significantly higher than pre-test scores (p<0.001). The programme positively influenced the respondents' self-efficacy scores. As perceived by the respondents, the preceptorship programme had a positive effect and improved their clinical performance in the nursing process. There was no relationship between perceived competence and respondents' demographic profiles. Conclusions: Reporting on self-efficacy in clinical practice may not be the most effective, reliable or accurate measure or evaluation of clinical performance since self-scoring may be affected by existing cultural implications and a strong sense of self-efficacy. The self-scoring results may be followed by qualitative information, like interviews, to determine respondents' knowledge of the nursing process, direct observation of performance in the clinical area and care outcomes, and confirm if the respondents' clinical performance matches the obtained results.